SGLT-2 inhibitors in heart failure: a literature review on mechanisms, efficacy and safety - Klaudia Kułak; Katarzyna Chamera-Cyrek; Izabela Janik; Martyna Kuśmierska; Anna Koman; Marzena Pliszka; Katarzyna Gadżała; Karolina Palacz; Izabela Sztybór; Sabina Przygodzka (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Sodium-glucose cotransporter-2 inhibitors (SGLT2 inhibitors), known as flozins, are a recent class of medications gaining recognition for their effectiveness in diabetes, cardiovascular health, and heart failure management. The objective of this study is to examine and integrate recent literature concerning the mechanisms, effectiveness, and safety of SGLT2 inhibitors in managing heart failure. Material and Methods of Research: A literature review focused on keywords related to the topic was performed using databases such as PubMed and Google Scholar. Results: SGLT-2 inhibitors, initially developed for type 2 diabetes, significantly benefit heart failure (HF) with reduced, mildly reduced, and preserved ejection fractions by improving various cardiac outcomes. These drugs lower glucose levels and promote osmotic diuresis, natriuresis, and favorable metabolic effects, reducing cardiac preload and afterload. Consequently, SGLT-2 inhibitors are now pivotal in HF treatment, enhancing cardiac efficiency and reducing HF-related hospitalizations and mortality. Conclusion: SGLT-2 inhibitors substantially decrease cardiovascular risk and hospitalizations for heart failure in patients with or without type 2 diabetes, making them crucial in HF management. Consequently, SGLT-2 inhibitors should be considered first-line therapy for heart failure, regardless of concurrent medications, due to their efficacy and comprehensive benefits in managing this condition.